(untitled) (Bangladesh Journal of Child Health, 2014)
Background: Appropriate breastfeeding and complementary feeding practices are the fundamental to childrens nutrition, health and survival during the first year of life. WHO and UNICEF have articulated a global strategy for poor infant feeding practices directly and indirectly contributes to under nutrition, morbidity and mortality in infant. Objective: This study was designed to determine the breast feeding (BF) and complementary feeding (CF) practices in study population. Methodology: This descriptive cross sectional study was carried out in Pediatrics out patients department (OPD) of Shahid Surhawardy Medical College and Hospital, from January 2009 to December 2009. Feeding history of total 250 babies age >6 months to <1 year was taken from mothers. Results: Among 250 total babies, prelacteal feed was given in 29.2%(73/250), colostrum was given in 79.2%(198/250) and exclusive breast feeding upto six months was given in 24%(60/250) babies. CF was started in 242 babies and it was too early before six months in 29.6%(74/250) cases. Amount of CF was adequate in 66.9%(162/ 242) and composition of CF was good enough in 58.3%(141/242) babies. Conclusion: In this study CF was introduced before 6 months in one third babies and amount was inadequate in same numbers of children. There is need for promotion and protection of optimal infant feeding practices for improving nutritional status of our children. DOI: http://dx.doi.org/10.3329/bjch.v37i3.18616 Bangladesh J Child Health 2013; Vol.37(3): 138-141